2009
DOI: 10.1016/j.neuropsychologia.2009.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for incremental lexical-semantic integration in auditory compound comprehension

Abstract: The present study investigated the time-course of semantic integration in auditory compound word processing. Compounding is a productive mechanism of word formation that is used frequently in many languages. Specifically, we examined whether semantic integration is incremental or is delayed until the head, the last constituent in German, is available. Stimuli were compounds consisting of three nouns, and the semantic plausibility of the second and the third constituent was manipulated independently (high vs. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
5
12
0
Order By: Relevance
“…In addition, they found that parsing choice for ambiguous compounds is driven by the relative semantic plausibility of the parses (e.g., clamp+rod and clam+prod). This result is not restricted to ambiguous novel compounds; Koester, Holle, and Gunter (2009) found that German three-word compounds with plausible constituents were easier to interpret than were compounds with less plausible constituents.…”
mentioning
confidence: 82%
“…In addition, they found that parsing choice for ambiguous compounds is driven by the relative semantic plausibility of the parses (e.g., clamp+rod and clam+prod). This result is not restricted to ambiguous novel compounds; Koester, Holle, and Gunter (2009) found that German three-word compounds with plausible constituents were easier to interpret than were compounds with less plausible constituents.…”
mentioning
confidence: 82%
“…Moreover, since N400 has been argued to reflect aspects of combinatorial processing (German: Holle et al, 2010; Koester et al, 2007, Koester et al, 2009; Chinese: Bai et al, 2008; see also Vergara-Martínez, Duñabeitia, Laka, & Carreiras, 2009, for attribution of N400 to selectional/integrational processing in Basque visually-presented compounds), it is possible that some aspects of the combinatoric processing of lexicalized and novel English compounds may also engender increased negativities in the N400 (or, as described in some of the literature, an N400-like negativity). However, it is also possible that some aspects of the combinatoric processing of lexicalized and/or novel compounds may engender anterior negativities (i.e., LAN effects; note that responses attributed in the literature to LAN often extend beyond the Left Anterior region into other anterior regions, and even extend sometimes to posterior regions).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, these studies suggest that constituent access (Holle et al, 2010) and compositional processing may engender N400 effects (Holle et al, 2010; Koester et al, 2007, 2009; Bai et al, 2008). These studies thus converge in suggesting that N400-like negativities may indeed reflect aspects of morphological decomposition and post-decompositional, combinatoric operations.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Responses to morphological violations such as the incorrect use of verbal inflection have also been evidenced to elicit specific ERP response components, independent from semantic or syntactic lexical errors (Friederici, Pfeifer, & Hahne, 1993). Furthermore, compound words that consist of two free stems (e.g., teacup) also http appear to be decomposed into their constituents and incrementally integrated (Koester, Holle, & Gunter, 2009), aided by prosodic information (Koester, 2014).…”
Section: Routes To Word Recognitionmentioning
confidence: 99%